2004
DOI: 10.1590/s1516-35982004000900027
|View full text |Cite
|
Sign up to set email alerts
|

Composição centesimal da carne de cordeiros Santa Inês puros e de seus mestiços com Texel abatidos com diferentes pesos

Abstract: RESUMO -Objetivou-se avaliar a composição centesimal da carne de cordeiros da raça Santa Inês (SI x SI) e de seus mestiços com Texel (T x SI), abatidos com diferentes pesos vivos. O músculo biceps femoris foi utilizado para as análises de umidade, de proteína bruta (PB), de extrato etéreo (EE) e de cinzas. O delineamento foi inteiramente casualizado, com 16 tratamentos, em esquema fatorial 2x2x4, com dois grupos genéticos, dois sexos (14 machos e 13 fêmeas em cada grupo) e quatro pesos de abate (15, 25, 35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
0
6
1
7
Order By: Relevance
“…These values are high when compared to the results found by Bonagurio, Perez and Garcia (2001), who described mean values of 1.0 to 3.5 g.100 g -1 in lambs' muscles. However, it should be emphasized that in the present experiment, the contents were obtained from samples of the edible portion (muscle and fat) of the shoulder, instead of only one type of muscle.…”
Section: Discussioncontrasting
confidence: 49%
“…These values are high when compared to the results found by Bonagurio, Perez and Garcia (2001), who described mean values of 1.0 to 3.5 g.100 g -1 in lambs' muscles. However, it should be emphasized that in the present experiment, the contents were obtained from samples of the edible portion (muscle and fat) of the shoulder, instead of only one type of muscle.…”
Section: Discussioncontrasting
confidence: 49%
“…Russo et al (1999) showed that weight at slaughter influences the chemical composition of meat, as heavier sheep deposit more fat and, as a result, exhibit a lower amount of water and protein in their meat. Bonagurio et al (2004) examined the composition of pure Santa Ines sheep and their crossbreeds slaughtered at different weights and came to a similar conclusion: with an increase in slaughter weight, there is a decrease in the amount of moisture, which is associated with a tendency for the reduction in the amount of crude protein. However, this effect was not observed in this study, where it was found that variation in weight at slaughter did not influence the chemical composition of the meat.…”
Section: Resultsmentioning
confidence: 85%
“…Therefore, higher SFH levels in the diet promote increase in the moisture content of meat (Bonagurio et al, 2004).…”
Section: Resultsmentioning
confidence: 99%